Antarctic NAT PSC Belt of June 2003: Observational Validation of the Mountain Wave Seeding Hypothesis - Eckermann, S. D.; Hoffmann, L.; Hoepfner, M.; Wu, D. L.; Alexander, M. J. (2009)
Satellite observations of polar stratospheric clouds (PSCs) over Antarctica in June 2003 revealed small nitric acid trihydrate (NAT) particles forming suddenly along the vortex edge. Models suggest the trigger was mountain waves over the Antarctic Peninsula (AP) forming ice for NAT nucleation. We test this hypothesis by analyzing perturbations in stratospheric radiances from the Atmospheric Infrared Sounder (AIRS). AIRS data show mountain waves over the AP on 10-14 June, with no resolved wave activity before or after. Peak wave temperature amplitudes derived from independent 40 hPa channels all return values of 10-12 K, in agreement with values used to model this NAT event. These observations support a NAT wake from a small region of mountain wave activity over the AP as the source of this circumpolar NAT outbreak. Published in Geophysical Research Letters, v36 nL02807 p1-4, 2009. Performed in collaboration with Forschungszentrum Juelich, Germany; Forschungszentrum Karlsruhe, Germany; California Institute of Technology, Pasadena, CA; and Northwest Research Associates, Boulder, CO.